Education and Training on Making Probiotic Drinks to Help Improve Health and Immunity in Bantarsari Village - Wulandari, Asri; Wulandari, Cyntia; Nurhikmah, Wilda; Koniah, Eni; Tri Retno, Marybet; Permanasari, Anna; Oktaviani, Emy; Herlina, Nina; Ashura Rizkiyani, Nanda (Jurnal Pengabdian Masyarakat Inovatif, 2023)
Infectious diseases are still a global problem, including in Indonesia. Immunity is an important factor in preventing infectious diseases. Probiotics are living organisms that are able to provide beneficial effects for maintaining health, namely being able to maintain the health of the digestive tract so that the body's immunity becomes better. The purpose of this community service is to provide information and increase knowledge about the role of probiotics in helping improve health and body immunity to mothers who live in Bantarsari Village, Rancabungur District, Bogor Regency. The method used is initial pretest followed by providing education about probiotics, giving brochures about probiotics, demonstrating the manufacture of probiotics and closing with post test to see the final ability of the participants. The result of the community service activity is an increase in the knowledge of the participant mothers about the importance of probiotics, types of probiotics and an increase in the ability to make probiotic drinks. The activity went well and was attended by the target group community and followed by village officials.